OXYTOCIN-INDUCED CONTRACTIONS OF THE RABBIT CORPUS CAVERNOSUM - (:unkn) unknown (ELSEVIER SCIENCE BV, 1995)
The contractile effect of oxytocin on isolated rabbit corpus cavernosum strips was investigated. Concentration-response curves to oxytocin and phenylephrine were obtained. Oxytocin repetitively induced concentration-dependent contractions in the corpus cavernosum strips. The maximal contractile response to oxytocin was in amplitude 39.4 +/- 9.1% of that to phenylephrine. The slopes of the concentration-response curves, the amplitude of the maximal contractile effects, and the pD(2) values of oxytocin obtained in endothelium-denuded strips were not significantly different from those of intact preparations. The results of this study demonstrated that oxytocin contracts the rabbit corpus cavernosum, but the endothelium does not contribute to this effect. Since oxytocin is less efficacious than phenylephrine, it seems unlikely that this hormone can serve as an alternative in the treatment of prolonged penile erections.
Keywords: CORPUS CAVERNOSUM, RABBIT; ERECTION; IMPOTENCE; OXYTOCIN; CEREBROSPINAL-FLUID; MALE-RAT; VASOPRESSIN; ENDOTHELIN; SECRETION; TISSUE; PLASMA